Therapeutic Response to PRRNT in a Rare Case of Metastatic Renal Neuroendocrine Carcinoma - Sunny, Saumya Sara; Hephzibah, Julie; Chacko, Raju Titus; Kodiatte, Thomas Alex (World Journal of Nuclear Medicine, 2024)
Neuroendocrine tumors (NETs) are a rare spectrum of neoplasms that are characterized by neuroendocrine and neural differentiation. The treatment can be challenging in view of the heterogeneity in differentiation and behavior. Primary renal origin NETs are rare and only a few cases have been reported in the literature. There is limited knowledge on their presentation and response to various lines of treatment. We report a case of a patient with a metastatic renal NET from a rare histological subtype of large cell neuroendocrine carcinoma, known to cause aggressive disease with poor prognosis. A multimodality treatment approach was followed. In spite of surgical management and second-line chemotherapy, the disease progressed. The patient subsequently received peptide receptor radionuclide therapy (PRRNT) using lutetium-177 DOTATATE, following which the patient demonstrated a remarkable clinical and radiological response and is stable to date. In a rare tumor with poor prognosis, the relevance of theranostics and the efficacy of targeted therapies like PRRNT are noteworthy.
Keywords: neuroendocrine tumors; peptide receptor radionuclide therapy; theranostics; lutetium-177; DOTATATE